Change creation or harnessing nature: the reception of biotechnology in Islamic world - Bouzenita, Anke Sandra (Islamic Research Institute (IRI), 2009)
This paper deals with the reception of biotechnology in the Islamic world, particularly focusing on the characteristics of the reception of biotechnology by Muslim legal scholars (fuqahā'), with reference to the general societal discourse. It elucidates the relationship between Islam and Science as an essential paradigm to understand the current discourse on biotechnology. The paper describes the related paradigm shift which has taken place in the Islamic world and deliberates whether or not this paradigm shift has been taken into account in the contemporary discourse on the subject. While attempting to carefully study human cloning and genetically modified food, the paper critically analyses the role of the maqāsid (objectives) of the shari'ah in this discourse. It also offers a glimpse of policy making in the Islamic world in the field of biotechnology. The paper arrives at the conclusion that recourse to the maqāsid scheme is liable to be instrumental in promoting utilitarian ends rather than the ideals of the shari'ah.